Australian general practice registrars perceived development of cultural safety for Indigenous patients: A qualitative study - Kay Brumpton; Hannah Woodall; Rebecca Evans; Henry Neill; Tarun Sen Gupta; Lawrie McArthur; Raelene Ward (PLoS ONE, 2025)
Objective It is poorly understood how general practice registrars develop skills towards providing culturally safe care to Indigenous patients. Finding ways to enable the patient to determine culturally safe care, but not be responsible for teaching or correcting, is a challenge for health education systems. This study aims to explore how Australian general practice registrars perceive they develop towards cultural safety in readiness to consult with Aboriginal and Torres Strait Islander patients. Design This study utilised a pragmatic philosophical position. It is a qualitative study involving administration of a survey for demographic details alongside semi-structured interviews to explore how general practice registrars develop towards cultural safety. Data collection was conducted from March to August 2022. Transcripts were studied using a content analysis approach. Setting Regional Queensland, Australia. Participants General practice registrars Results Sixteen registrars completed the survey and semi-structured interview. Registrars described four main factors that contribute towards their development of cultural safety: shared or similar life experiences, learning from cultural safety training, experiential learning, and critical reflection. Registrars thought it was acceptable for patients to educate, teach or correct culturally unsafe care and did not reflect on the power imbalance in these relationships. Conclusion Cultural safety appears to be a lifelong learning journey balancing critical self-reflection against an external determination of cultural safety. Understanding this process warrants further research and review of medical education teaching.